1996
DOI: 10.1016/s0092-8674(00)81280-5
|View full text |Cite
|
Sign up to set email alerts
|

Cell Migration: A Physically Integrated Molecular Process

Abstract: to integrate comes from in vitro studies, mainly concerning movement across two-dimensional substrata. We *Center for Biomedical Engineering and Department of Chemical Engineering nonetheless believe that much of the mechanistic understanding is relevant and useful for in vivo situations even Massachusetts Institute of Technology Cambridge, Massachusetts 02139 in three dimensions. It is likely that cells interact with their surroundings by means of the same types of recep- † Department of Cell and Structural B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

54
2,952
3
19

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,621 publications
(3,028 citation statements)
references
References 100 publications
54
2,952
3
19
Order By: Relevance
“…Namely, Taniuchi et al (2005) showed that a pancreatic cancer cell line, transfected with wild-type P-cadherin, migrated faster than the cells without this molecule. Epithelial cell migration requires the coordination of three basic cellular processes: actin cytoskeleton reorganization, matrix adhesion and matrix re-modelling (Lauffenburger and Horwitz, 1996;Fenteany et al, 2000). In this present study, we also show, by time-lapse microscopy and actin phalloidin staining, that P-cadherin is able to induce phenotypic changes involving alterations in cell polarity and leading edge morphology, formation of membrane protrusions, as well as, increase of their cytoplasmic area, which usually is characteristic from cells with a motile behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, Taniuchi et al (2005) showed that a pancreatic cancer cell line, transfected with wild-type P-cadherin, migrated faster than the cells without this molecule. Epithelial cell migration requires the coordination of three basic cellular processes: actin cytoskeleton reorganization, matrix adhesion and matrix re-modelling (Lauffenburger and Horwitz, 1996;Fenteany et al, 2000). In this present study, we also show, by time-lapse microscopy and actin phalloidin staining, that P-cadherin is able to induce phenotypic changes involving alterations in cell polarity and leading edge morphology, formation of membrane protrusions, as well as, increase of their cytoplasmic area, which usually is characteristic from cells with a motile behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Bundling of the actin cytoskeleton and its intracellular distribution directly determine cell motility. 5 a-Actinin has been recognized to cross-link actin filaments, and two types of non-muscular a-actininactinin-1 and actinin-4-have been identified. 30 Actinin-1, specifically localized at the ends of actin stress fibers, is thought to be associated with cell adhesion molecules such as integrin-b and a-catenin, and plays an important role in stabilizing cell adhesion, thus regulating cell shape and cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…4 Various molecular components of the cytoskeleton, cell adhesion, and signaling systems seem to be involved in the regulation of cell motility. [5][6][7][8] Actinin-1 is an isoform of non-muscular a-actinin preferentially localized on the inner surface of cells, being a component of focal adhesion plaques and cell-to-cell adherence junctions. Actinin-4, another isoform of non-muscular a-actinin, was recently identified as an actin-bundling protein.…”
mentioning
confidence: 99%
“…17 This landscape directs attachment and detachment to and from the ECM, controls the geometry of the cell niche, and regulates cytoskeletal organization, which all influence tissue formation, cell fate, wound repair, and cancer metastasis. 18 In short, cells exert contractile forces as they actively engage with the ECM introducing tensile stresses in the cytoskeleton that originate at focal adhesions and it is now evident that both dynamic adhesion and force generation play a major role in directing cell function. 14 …”
Section: Introductionmentioning
confidence: 99%